Responsibility and Mindset of Tourist and Community-Based Tourism Enterprise to Conserve the Environment and Energy - Sudjai Jirojkul (UIKTEN, 2021)
The aim of the research is to assess the mindset, activities and the participation of communitybased tourism enterprises in the tourists’ awareness and behavior. Tourism has the significant impact in order to develop the guideline for organizing the activities and managing the community-based tourism in reflecting the responsible environment and energy linking character and behavior of tourists. We found a strong growth mindset of entrepreneur’s community as the key factor that affected on driving the participation of tourism management. Mindset was a significant mechanism to motivate and encourage sustainable tourism in the future. Finally, it represents the responsible environment and energy systematically.